Gender Difference in Presentation, Management and Inhospital Mortality in St Elevation Myocardial Infarction in a Tertiary Cardiac Center (Journal of Nobel Medical College, 2015)
Background: Studies have shown that women are less likely to receive reperfusion therapy and have higher inhospital death in ST Elevation myocardial infarction(STEMI) as compared to men. This study aims to examine presentation, acute therapy, and inhopital mortality in women admitted with diagnosis of acute STEMI in a tertiary care cardiac center.Methods: Patients admitted with diagnosis of acute STEMI from 1st June 2013 to 31st May 2015 were included in the study. Gender difference in baseline characterstics, comorbidities, prehospital delay, type of treatment received and inhospital death were measured. Variables that might have impact on inhospital deaths were analyzed on multivariate regression analysis to find out other variables adjusted effect of gender on inhospital deaths.Results : Majority of the patients were men (Men 69% vs women 31%). Women were older, were more likely to be diabetics and smoker. Prehospital delay was more in women ( women 22 hours vs men 12 hours, p value-0.02).About 46% of both men and women received reperfusion therapy. There was more inhospital mortality in women (women 13.5% vs men 6.5%, p value – 0.02). Women had more inhospital mortality even after adjustment with other covariables (OR = 3.110, 95% CI = 1.411-6.902, p value-0.005).Conclusion : Women were more likely to be elderly, diabetics, smoker and presented later than men after symptoms onset. Women received reperfusion therapy similar to that of men. After adjustment with other covariates, women remained a significant variable to inhospital death.Journal of Nobel College of Medicine Vol.4(1) 2015: 6-11